Identifying Factors Motivating Users to Post Reviews on Online Travel Review Platforms: A Factor Analysis Study - Sharma, Animesh; Sharma, Rahul (Mercados y Negocios, 2025)
This research paper aims to identify the factors motivating users to post reviews on online travel review platforms (OTRPs). A non-probabilistic sampling technique, purposive sampling, was employed for data collection. Exploratory Factor Analysis (EFA) was conducted on a dataset of 1,313 observations. This study highlights several pivotal factors encouraging users to engage in this review-sharing phenomenon. Three key factors, social recognition and connection, enhancing travel experiences, and social validation, were identified as motivating users to write online reviews. Among these, the innate desire for social connection, the building of social capital, and the inclination to offer peer support emerge as the predominant motivations driving users’ intentions to create travel-related reviews on online platforms. By analyzing the complex interplay of psychological, social, and support-based incentives, this study not only contributes to adds body knowledge to the literature of motivation theories but also offers practical guidance to online travel agencies (OTAs) managers in their pursuit of providing exceptional customer experiences and marketing strategies in an era of expanding online travel. This study assists OTAs in understanding customer experiences, tailoring services to meet travelers’ expectations, and delivering enriching customer interactions.